Exchange Rate Policies, Prices and Supply-Side Response A Study of Transitional Economies - Papazoglou, Christos; Pentecost, Eric J. (Palgrave Macmillan UK, 2001)
This book, based upon a large-scale research project, examines alternative types of exchange rate policies being pursued and the changing nature of exchange rate policy during the transition process in four countries, Slovenia, Bulgaria, Poland and the Czech Republic. The book brings together a series of original contributions by country experts and draws out some common themes and over-arching policy implications for the operation of exchange rate policy in the transition process
Keywords: International business enterprises; Trade; Business; Commerce; Banks and banking; Macroeconomics; International economics; Economics